2014
DOI: 10.3389/fnins.2014.00261
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of lactate into, from, and among gap junction-coupled astrocytes and their interaction with noradrenaline

Abstract: Lactate is a versatile metabolite with important roles in modulation of brain glucose utilization rate (CMRglc), diagnosis of brain-injured patients, redox- and receptor-mediated signaling, memory, and alteration of gene transcription. Neurons and astrocytes release and accumulate lactate using equilibrative monocarboxylate transporters that carry out net transmembrane transport of lactate only until intra- and extracellular levels reach equilibrium. Astrocytes have much faster lactate uptake than neurons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 69 publications
1
41
0
Order By: Relevance
“…Further, if exogenous lactate is not supplied in such experiments, cultured neurons release lactate to the extracellular medium following depolarization events [22]. This may be consistent with the opinion presented in a recent review by Hertz et al [26] in which both neurons and astrocytes release and accumulate lactate during brain activation until a new intra-extracellular equilibrium is reached; lactate may then be dispersed within the astrocytic syncytium and eventually to some extent be discharged from the brain accounting for the observed uncoupling of glucose and oxygen consumption during brain activation [27]. Further, we have previously found that lactate alone is a poor substrate in terms of supporting synaptic transmission, since re-uptake of released neurotransmitter glutamate in cultured glutamatergic neurons fails [8].…”
Section: Discussionsupporting
confidence: 84%
“…Further, if exogenous lactate is not supplied in such experiments, cultured neurons release lactate to the extracellular medium following depolarization events [22]. This may be consistent with the opinion presented in a recent review by Hertz et al [26] in which both neurons and astrocytes release and accumulate lactate during brain activation until a new intra-extracellular equilibrium is reached; lactate may then be dispersed within the astrocytic syncytium and eventually to some extent be discharged from the brain accounting for the observed uncoupling of glucose and oxygen consumption during brain activation [27]. Further, we have previously found that lactate alone is a poor substrate in terms of supporting synaptic transmission, since re-uptake of released neurotransmitter glutamate in cultured glutamatergic neurons fails [8].…”
Section: Discussionsupporting
confidence: 84%
“…from astrocytes to neurons [33]. It is, however, consistent with a more nuanced view of lactate dynamics where extracellular lactate originates from, and is metabolized by, multiple cell types, where lactate is scattered from the activated brain area via the astrocytic syncytium [34], and where lactate plays roles other than that of an energy substrate, e.g. redox signaling to switch on neuronal plasticity genes [35].…”
Section: Malate Aspartate Shuttle In Isolated Brain Mitochondria and mentioning
confidence: 52%
“…1e, f). In addition, it is known that lactate is most likely produced and to some extent released from both neurons and astrocytes during brain activation [29]. Therefore, brain lactate could be from blood lactate uptake, …”
Section: Discussionmentioning
confidence: 99%